Investigating the best practice of teachers in conflict management, MARA Education Institutions, Malaysia - Salleh, Mohamad Johdi (International Institute for Science, Technology & Education (IISTE), 2013)
This study attempts to investigate the views, processes, and, best practice of conflict management among the MARA - Majlis Amanah Rakyat or Board of People Trust – teachers in the MARA education institutions. The sample of the study was 306 teachers conveniently selected from MARA education institutions in Malaysia. The data was processed using the Statistical Package for Social Science (SPSS) version 17.0 for Windows. The finding shows that the highest perception of MARA teachers was ‘conflict can be thought as problem, we need to find the source and take the appropriate steps to solve it’ mean 4.40 and SD 0.585. In relation to the process of managing conflict, the perception was highest on ‘solution finding process is needed in conflict management’ mean 4.29 and SD 0.698. Finally, the finding indicates that the best practice of conflict management among MARA teachers was ‘conflict can be solved if there is understanding between parties and find the solution together’ mean 4.40 and SD 0.618. It is believed that if the teachers regardless of background can manage effectively the conflict in schools or colleges and foster healthy teacher-administrator relationship, teaching and learning can be improved towards facing the challenges in the era of globalization and realization of vision 2020, Malaysia, and beyond.